2010
DOI: 10.1080/0361073x.2010.509010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function, Physical Performance, Health, and Disease: Norms From the Georgia Centenarian Study

Abstract: This study provides, for the first time, normative data on cognitive functioning and physical performance, health and health behaviors, and diseases from a population-based sample of 244 centenarians and near-centenarians (M age = 100.5 years, range 98-108, 84.8% women, 21.3% African American) from the Georgia Centenarian Study. Data are presented by the four key dimensions of gender, race, residence, and educational attainment. Results illustrate the profound range of functioning in this age group and indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 36 publications
8
58
1
Order By: Relevance
“…Results concerning the 90+ age band should be considered cautiously as there were only 57 participants in this age band; this information was included despite this limitation because it highlights the range of ages within the FHS sample. The number of individuals in this group is likely to grow and will be included in future studies; it is of interest that though this data is preliminary, cognition does appear to continue to change at this advanced age, which supports recent studies of cognitive changes even among centenarians (Davey et al, 2013; Davey et al, 2010; Miller et al, 2010). These results are generally similar to those reported by Welsh-Bohmer and colleagues and Elias and co-authors (Elias et al, 2011; Welsh-Bohmer et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Results concerning the 90+ age band should be considered cautiously as there were only 57 participants in this age band; this information was included despite this limitation because it highlights the range of ages within the FHS sample. The number of individuals in this group is likely to grow and will be included in future studies; it is of interest that though this data is preliminary, cognition does appear to continue to change at this advanced age, which supports recent studies of cognitive changes even among centenarians (Davey et al, 2013; Davey et al, 2010; Miller et al, 2010). These results are generally similar to those reported by Welsh-Bohmer and colleagues and Elias and co-authors (Elias et al, 2011; Welsh-Bohmer et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…For example, Ahl and coauthors (2013) found that in the Framingham Offspring cohort, MCI as defined by WRAT-adjusted as compared to education-adjusted norms was more strongly associated with incident dementia for all cognitive tests examined (Ahl et al, 2013). Their suggestion of using reading level as a more accurate surrogate than years of formal education has been supported by other studies of the oldest-old (Davey et al, 2013; Davey et al, 2010; Elias et al, 2011). The influence of reading level on cognitive performance has been found in other populations as well.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations